Characterization of epidemic clones of Listeria monocytogenes serotype 4b isolated from humans and meat products in Brazil - Barbosa, André Victor (2015)
Universidade Federal Fluminense. Departamento de Microbiologia e Parasitologia. Laboratório de Enteropatógenos, Microbiologia Veterinária e de Alimentos. Niterói, RJ, Brasil / Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Laboratório de Zoonoses Bacterianas. Rio de Janeiro, RJ, Brasil.